Contribution of mushroom production for better environment, nutrition and health - Attri, B L; Srivastava, Anuradha; Bijla, Shweta; Kamal, Shwet; Sharma, V P (Indian Horticulture, 2022)
Mushroom, a super food suitable for all age groups, contains all the vital nutrients required for human body in desired proportion. The production of mushrooms in India has increased by an average growth rate of 8.3% in last 25 years. Different types of mushrooms viz. white button (Agaricus bisporus), oyster (Pleurotus spp.), paddy straw (Volvariella volvacea), milky (Calocybe indica) and shiitake (Lentinula edodes) mushroom with a total production of about 2.43 lakh tonnes are being cultivated on commercial scale in India because of its diversified agro-climatic conditions. Mushrooms have been recognized to contain highest and quality protein per unit area from agro-wastes generating employment, improving economic status of growers, checking pollution and earning foreign exchange. They also restore the environment by playing a role in degrading the pesticides and persisting chemicals. The spent mushroom substrate after cropping, remain as a good source of protein and other nutrients for animal feed. Mushrooms with their good nutritional, medicinal and functional properties are considered as a health food as they contain low calories, high protein, dietary fibre, vitamins, and minerals with high antioxidant capacity. Hence, mushroom cultivation is an effective way for resource poor farmers to generate wealth from waste using a limited space within a short duration. It also provides an opportunity to produce a highly tradable commodity, thereby contributing to income generation and improved socio-economic status.